Answer:
a
![y(t) = y_o e^{\beta t}](https://tex.z-dn.net/?f=y%28t%29%20%3D%20y_o%20e%5E%7B%5Cbeta%20t%7D)
b
![x(t) = x_o e^{\frac{-\alpha y_o }{\beta }[e^{-\beta t} - 1] }](https://tex.z-dn.net/?f=x%28t%29%20%3D%20%20x_o%20e%5E%7B%5Cfrac%7B-%5Calpha%20y_o%20%7D%7B%5Cbeta%20%7D%5Be%5E%7B-%5Cbeta%20t%7D%20-%201%5D%20%7D)
c
![\lim_{t \to \infty} x(t) = x_oe^{\frac{-\alpha y_o}{\beta } }](https://tex.z-dn.net/?f=%5Clim_%7Bt%20%5Cto%20%5Cinfty%7D%20x%28t%29%20%3D%20x_oe%5E%7B%5Cfrac%7B-%5Calpha%20y_o%7D%7B%5Cbeta%20%7D%20%7D)
Step-by-step explanation:
From the question we are told that
![\frac{dy}{y} = -\beta dt](https://tex.z-dn.net/?f=%5Cfrac%7Bdy%7D%7By%7D%20%3D%20%20-%5Cbeta%20dt)
Now integrating both sides
![ln y = \beta t + c](https://tex.z-dn.net/?f=ln%20y%20%20%3D%20%20%5Cbeta%20t%20%2B%20c)
Now taking the exponent of both sides
![y(t) = e^{\beta t + c}](https://tex.z-dn.net/?f=y%28t%29%20%3D%20%20e%5E%7B%5Cbeta%20t%20%2B%20c%7D)
=> ![y(t) = e^{\beta t} e^c](https://tex.z-dn.net/?f=y%28t%29%20%3D%20%20e%5E%7B%5Cbeta%20t%7D%20e%5Ec)
Let ![e^c = C](https://tex.z-dn.net/?f=e%5Ec%20%3D%20%20C)
So
![y(t) = C e^{\beta t}](https://tex.z-dn.net/?f=y%28t%29%20%3D%20C%20e%5E%7B%5Cbeta%20t%7D)
Now from the question we are told that
![y(0) = y_o](https://tex.z-dn.net/?f=y%280%29%20%3D%20%20y_o)
Hence
![y(0) = y_o = Ce^{\beta * 0}](https://tex.z-dn.net/?f=y%280%29%20%3D%20y_o%20%20%3D%20Ce%5E%7B%5Cbeta%20%2A%200%7D)
=> ![y_o = C](https://tex.z-dn.net/?f=y_o%20%3D%20C)
So
![y(t) = y_o e^{\beta t}](https://tex.z-dn.net/?f=y%28t%29%20%3D%20y_o%20e%5E%7B%5Cbeta%20t%7D)
From the question we are told that
![\frac{dx}{dt} = -\alpha xy](https://tex.z-dn.net/?f=%5Cfrac%7Bdx%7D%7Bdt%7D%20%20%3D%20-%5Calpha%20xy)
substituting for y
![\frac{dx}{dt} = - \alpha x(y_o e^{-\beta t })](https://tex.z-dn.net/?f=%5Cfrac%7Bdx%7D%7Bdt%7D%20%20%3D%20-%20%5Calpha%20x%28y_o%20e%5E%7B-%5Cbeta%20t%20%7D%29)
=> ![\frac{dx}{x} = -\alpha y_oe^{-\beta t} dt](https://tex.z-dn.net/?f=%5Cfrac%7Bdx%7D%7Bx%7D%20%20%3D%20-%5Calpha%20y_oe%5E%7B-%5Cbeta%20t%7D%20dt)
Now integrating both sides
![lnx = \alpha \frac{y_o}{\beta } e^{-\beta t} + c](https://tex.z-dn.net/?f=lnx%20%3D%20%5Calpha%20%5Cfrac%7By_o%7D%7B%5Cbeta%20%7D%20e%5E%7B-%5Cbeta%20t%7D%20%2B%20c)
Now taking the exponent of both sides
![x(t) = e^{\alpha \frac{y_o}{\beta } e^{-\beta t} + c}](https://tex.z-dn.net/?f=x%28t%29%20%3D%20e%5E%7B%5Calpha%20%5Cfrac%7By_o%7D%7B%5Cbeta%20%7D%20e%5E%7B-%5Cbeta%20t%7D%20%2B%20c%7D)
=> ![x(t) = e^{\alpha \frac{y_o}{\beta } e^{-\beta t} } e^c](https://tex.z-dn.net/?f=x%28t%29%20%3D%20e%5E%7B%5Calpha%20%5Cfrac%7By_o%7D%7B%5Cbeta%20%7D%20e%5E%7B-%5Cbeta%20t%7D%20%7D%20e%5Ec)
Let ![e^c = A](https://tex.z-dn.net/?f=e%5Ec%20%20%3D%20%20A)
=> ![x(t) =K e^{\alpha \frac{y_o}{\beta } e^{-\beta t} }](https://tex.z-dn.net/?f=x%28t%29%20%3DK%20e%5E%7B%5Calpha%20%5Cfrac%7By_o%7D%7B%5Cbeta%20%7D%20e%5E%7B-%5Cbeta%20t%7D%20%7D)
Now from the question we are told that
![x(0) = x_o](https://tex.z-dn.net/?f=x%280%29%20%3D%20%20x_o)
So
![x(0)=x_o =K e^{\alpha \frac{y_o}{\beta } e^{-\beta * 0} }](https://tex.z-dn.net/?f=x%280%29%3Dx_o%20%3DK%20e%5E%7B%5Calpha%20%5Cfrac%7By_o%7D%7B%5Cbeta%20%7D%20e%5E%7B-%5Cbeta%20%2A%200%7D%20%7D)
=> ![x_o = K e^{\frac {\alpha y_o }{\beta } }](https://tex.z-dn.net/?f=x_o%20%3D%20K%20e%5E%7B%5Cfrac%20%7B%5Calpha%20y_o%20%20%7D%7B%5Cbeta%20%7D%20%7D)
divide both side by ![(K * x_o)](https://tex.z-dn.net/?f=%20%28K%20%2A%20x_o%29)
=> ![K = x_o e^{\frac {\alpha y_o }{\beta } }](https://tex.z-dn.net/?f=K%20%3D%20x_o%20e%5E%7B%5Cfrac%20%7B%5Calpha%20y_o%20%20%7D%7B%5Cbeta%20%7D%20%7D)
So
![x(t) =x_o e^{\frac {-\alpha y_o }{\beta } } * e^{\alpha \frac{y_o}{\beta } e^{-\beta t} }](https://tex.z-dn.net/?f=x%28t%29%20%3Dx_o%20e%5E%7B%5Cfrac%20%7B-%5Calpha%20y_o%20%20%7D%7B%5Cbeta%20%7D%20%7D%20%2A%20%20e%5E%7B%5Calpha%20%5Cfrac%7By_o%7D%7B%5Cbeta%20%7D%20e%5E%7B-%5Cbeta%20t%7D%20%7D)
=> ![x(t)= x_o e^{\frac{-\alpha * y_o }{\beta} + \frac{\alpha y_o}{\beta } e^{-\beta t} }](https://tex.z-dn.net/?f=x%28t%29%3D%20x_o%20e%5E%7B%5Cfrac%7B-%5Calpha%20%2A%20y_o%20%7D%7B%5Cbeta%7D%20%2B%20%5Cfrac%7B%5Calpha%20y_o%7D%7B%5Cbeta%20%7D%20e%5E%7B-%5Cbeta%20t%7D%20%7D)
=> ![x(t) = x_o e^{\frac{\alpha y_o }{\beta }[e^{-\beta t} - 1] }](https://tex.z-dn.net/?f=x%28t%29%20%3D%20%20x_o%20e%5E%7B%5Cfrac%7B%5Calpha%20y_o%20%7D%7B%5Cbeta%20%7D%5Be%5E%7B-%5Cbeta%20t%7D%20-%201%5D%20%7D)
Generally as t tends to infinity ,
tends to zero
so
![\lim_{t \to \infty} x(t) = x_oe^{\frac{-\alpha y_o}{\beta } }](https://tex.z-dn.net/?f=%5Clim_%7Bt%20%5Cto%20%5Cinfty%7D%20x%28t%29%20%3D%20x_oe%5E%7B%5Cfrac%7B-%5Calpha%20y_o%7D%7B%5Cbeta%20%7D%20%7D)
A^2+b^2= c^2
3^2+4^2=c^2
9+16=c^2
25=c^2
5=c
C. First person -hellobrains
Answer:
the 1st one
Step-by-step explanation:
I passes it in the quiz
Answer:
Equation: ![30=2(x-2)+2(2x+3)](https://tex.z-dn.net/?f=30%3D2%28x-2%29%2B2%282x%2B3%29)
Step-by-step explanation:
By definition, the perimeter of a figure can be calculated by adding the lenghts of its sides.
Knowing this, you can write the following equation:
<em> [Equation 1]</em>
According to the data given in the exercise, the perimeter in feet of the fighter is:
![P=30](https://tex.z-dn.net/?f=P%3D30)
Therefore, you can substitute this values into<em> [Equation 1]:</em>
![30=2(x-2)+2(2x+3)](https://tex.z-dn.net/?f=30%3D2%28x-2%29%2B2%282x%2B3%29)
Finally, you must solve for "x" in order to find its value. This is:
![30=6x+2\\\\30-2=6x\\\\\frac{28}{6}=x\\\\x=\frac{14}{3}](https://tex.z-dn.net/?f=30%3D6x%2B2%5C%5C%5C%5C30-2%3D6x%5C%5C%5C%5C%5Cfrac%7B28%7D%7B6%7D%3Dx%5C%5C%5C%5Cx%3D%5Cfrac%7B14%7D%7B3%7D)